Reproductive pathophysiology of prepubertal buffalo heifers inoculated with Pasteurella multocida type B:2 and its immunogens (LPS and OMP) - Ibrahim, Hayder Hamzah (2016)
Haemorrhagic Septicaemia (HS) is an acute, highly fatal, septicaemic disease of bovines occurring in most tropical regions of Asia and Africa. Among bovines, buffaloes have been reported to be more susceptible than cattle following natural infection. This study was conducted in pre-pubertal female buffaloes experimentally infected by Pasteurella multocida type B:2 and its immunogens with the objectives of determining the changes in gonadotropin-releasing hormone (GnRH), follicle-stimulating hormone (FSH), luteinizing hormone (LH), progesterone, estrogen, interleukin-1β (IL-1β), interleukin 6 (IL-6) and tumour necrosis factor alpha (TNF-α) concentrations as well as pathological changes in the reproductive organs, mammary gland, supramammary lymph nodes and pituitary gland. Twenty-one clinically healthy pre-pubertal female buffalo calves of approximately eight months of age were selected for this study. The 21 buffalo calves were randomly divided into seven groups of three calves each. The seven treatment groups consisting of group 1 (three buffaloes) inoculated orally with sterile phosphate buffered saline (PBS) pH 7 (negative control group), group 2 (three buffaloes) inoculated with 1012 colony forming units (cfu) of P. multocida type B:2, orally, and group 3 (three buffaloes) inoculated with 1012 cfu of P. multocida B:2, subcutaneously. Buffaloes of group 4 (three buffaloes) and group 5 (three buffaloes) were inoculated with LPS extracted from P. multocida B:2 orally and intravenously, respectively . Groups 6 and 7 were inoculated with OMP extracted from P. multocida B:2, orally and intravenously, respectively. After inoculation, all the calves were monitored at 2 hour intervals for the clinical signs of HS for the first 12 hours and twice daily thereafter until the end of the experiment at day 21. At the end of the study surviving buffaloes were euthanised by exsanguination before post-mortem examination was carried out where reproductive organs (ovary, oviduct, uterine horn, uterine body, vagina, cervix), supramammary lymph nodes, mammary glands and pituitary glands were harvested for isolation and identification of P. multocida B:2 and histopathogical examination. The blood samples were collected for determination of concentrations of proinflammatory cytokines (IL1-β, IL-6 and TNF-α) and GnRH, LH, FSH, progesterone and estrogen. Buffaloes of groups 3 and 7 showed typical HS clinical signs and survived for the 12 hours and 72 hours respectively, while all buffaloes of groups 2, 4, 5 and 6 survived throughout the 21-day experiment and showed only mild clinical response of HS. Groups inoculated with Pasteurella multocida B:2 and its immunogens showed significant decrease (p<0.05) in the concentrations of GnRH, FSH and LH, progesterone and estrogen hormones compared to the control group and it was observed that subcutaneous routes of inoculation with Pasteurella multocida B:2 and its OMP groups 3 and 7 respectively led to a significantly low levels of production of these hormones in buffalo calves. IL-1β, IL-6 and TNF-α concentrations showed significant (p<0.05) increase post inoculation with Pasteurella multocida B:2 and its immunogens compared with control group and it was observed that subcutaneous routes of inoculation with Pasteurella multocida B:2 and its OMP group 3 and 7 respectively led to a significantly high level of cytokine production in buffalo calves. Microscopic examination showed significant congestion, infiltration of inflammatory cells, degeneration and necrosis in the reproductive organs, pituitary gland, supramammary lymph nodes and mammary gland and buffaloes of groups 3 and 7 showed significant changes compared with groups 2, 4, 5 and 6. Successful isolation and PCR confirmation of P. multocida B:2 was achieved from different parts of the reproductive system, including ovary, oviduct, uterine horn, uterine body and vagina as well as mammary glands and supramammary lymph nodes of the buffaloes inoculated subcutaneously with P. multocida B:2. Therefore, it can be concluded that P. multocida and its immunogens (LPS and OMP), had detrimental negative effects on GnRH, FSH, LH concentrations as well as oestrogen and progesterone concentration in all treated groups. Apart from these, cytokine concentrations showed significant increase in calves following inoculation with P. multocida type B:2 and its immunogens (LPS and OMP). The gross and cellular changes were of typical HS lesions following subcutaneous inoculation while the oral and intravenously inoculated group showed less cellular changes; therefore, this work provides strong evidence of the involvement of the female reproductive system of buffaloes during the pathogenesis of the disease and shows that route of inoculation strongly affects the localization of the bacterium in the reproductive system.